2023
DOI: 10.3390/jpm13050836
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sex Differences with Mortality and Organ Dysfunction in Patients with Sepsis and Septic Shock

Abstract: Background: Despite recent advances in the clinical management and understanding of sepsis and septic shock, these complex clinical syndromes continue to have high mortality rates. The effect of sex on these diseases’ mortality, clinical presentation and morbidity remains controversial. This study aimed to investigate the association of sex with mortality and organ dysfunction in patients with sepsis and septic shock. Methods: Prospectively enrolled patients with clinically defined sepsis and septic shock in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
3
2
0
Order By: Relevance
“…We found the SOFA components with the most notable sex-specific differences were those based on laboratory values with equal thresholds applied to men and women. Our findings corroborate previous results that found lower SOFA scores in respiratory and renal components in women, as well as lower serum bilirubin and creatinine [ 23 ]. Men in general have a higher muscle mass compared to women of comparable size, resulting in higher levels of creatinine [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found the SOFA components with the most notable sex-specific differences were those based on laboratory values with equal thresholds applied to men and women. Our findings corroborate previous results that found lower SOFA scores in respiratory and renal components in women, as well as lower serum bilirubin and creatinine [ 23 ]. Men in general have a higher muscle mass compared to women of comparable size, resulting in higher levels of creatinine [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found no differences in ICU mortality between women and men with sepsis or septic shock. This aligns with previous studies [ 23 , 37 ] and a meta-analysis [ 38 ] reporting no significant sex differences in short-term mortality in critically ill patients with sepsis and septic shock. Mewes et al demonstrated in their prospective study enrolling 737 septic patients that men exhibit more severe organ dysfunction according to SOFA and SOFA sub-scores, yet no sex differences were found in 28- and 90-day mortality [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previously described exclusion criteria were applied [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]: Age below 18 years; Pregnancy or breastfeeding; Immunosuppressive drugs and/or chemotherapy within six months prior to enrollment; History of myocardial infarction within six weeks before recruitment; New York Heart Association stage IV chronic heart failure; Human immunodeficiency virus (HIV) infection and/or hepatitis B/C infection; End-stage incurable disease; Persistent vegetative state (apallic syndrome); “Do Not Treat” or “Do Not Resuscitate” order; Participation in interventional studies; Family member of a study-site employee. …”
Section: Methodsmentioning
confidence: 99%
“…Previously described exclusion criteria were applied [15][16][17][18][19][20][21][22] Eligible patients were categorized according to their recent surgical history into surgical patients (including elective and emergency surgery) and non-surgical patients that did not undergo any type of surgical intervention. Surgical history included cardiac and non-cardiac surgery, including neurosurgery.…”
Section: Patient Enrollmentmentioning
confidence: 99%